Studies of recombinant streptococcal pyrogenic exotoxin B/cysteine protease (rSPE B/SCP) in the skin of guinea pigs & the release of histamine from cultured mast cells & basophilic leukocytes - Ohkuni, Hisashi; Todome, Yuko; Watanabe, Yukino; Ishikaw, Toshio; Takahashi, Hidemi; Kannari, Yutaka; Kato, Hidehito; Uchiyama, Takehiko; Saito, Hirohisa; Fischetti, Vincent A; Zabriskie, John B (Indian journal of medical research (New Delhi, India : 1994), 2004)
Streptococcal pyrogenic exotoxin B/streptococcal cysteine protease (SPE B/SCP) is considered to be one of the virulence factors of Streptococcus pyogenes (S. pyogenes) which causes serious diseases such as severe invasive infections and streptococcal toxic shock syndrome (STSS). There are no reports on the histamine releasing activity of SPE B/SCP from mast cells, although several biological activities have been studied. It is not clear whether SPE B/SCP have the superantigenic activity. We studied whether SPE B/SCP plays as a pathogenic factor in streptococcal infections and STSS through a histamine releasing activity. Human mast cells and basophils were generated from CD34 positive cells isolated from cord blood and cultured in the presence of rIL-6, stem cell factor and/or rIL-3. The capacity of increasing capillary permeability of recombinant SPE B/SCP (rSPE B/SCP) was studied by using the skin of guinea pigs. Mitogenic activity to human T-cells of rSPE B/SCP was studied by incorporation of (3)Hthymidine. The levels of histamine in the plasma of patients with STSS and controls were measured by ELISA kit. rSPE B/SCP induced increased capillary permeability in the skin of guinea pigs, but both SPE A and SPE C did not exhibit such activity. Histamine was released from cultured human mast cells stimulated with rSPE B/SCP. The rSPE B/SCP did not exhibit mitogenic activity to human T-cells. Three of the 7 patients with STSS showed higher levels of plasma histamine than those of normal subjects. The results suggested that increased capillary permeability and histamine release from mast cells induced by rSPE B/SCP might be involved in STSS and/or streptococcal infection of skin and mucous membrane.